PERBEDAAN ORIENTASI SEKSUAL SEBAGAI ALASAN PEMBATALAN PERKAWINAN PERSPEKTIF HUKUM POSITIF - Muh. Adistira Maulidi Hidayat; Muhammad Fadil Dzikru Rohmani; Magfira Aulia Zahra; Aden Rosadi (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2024)
Abstract: The goal of matrimony is the establishment of a lasting and harmonious family according to both legal and religious norms. On the other hand, if there are factors that can disrupt this union, then the marriage can be annulled according to the law. In essence, by nature, Allah SWT has created humans in pairs, between men and women, to build a family and procreate offspring. However, in some cases, there are individuals who contravene His rules by engaging in same-sex attraction, commonly referred to as LGBT (lesbian, gay, bisexual, and transgender). The following will further discuss LGBT as grounds for annulment of marriage according to both the Law and the Compilation of Islamic Law (KHI).